Comparative Analysis of the Color Stability of Different Ceramic Materials After Exposure to Staining Solutions - Sarita Aneja; Himani Painuly; Sajda K. Gajdhar; Shaiq Gajdhar; Vinay Rao; Jaskiran Kaur (Journal of Pharmacy and Bioallied Sciences)
Background: The color stability of ceramic dental materials is crucial for maintaining the aesthetic outcomes of dental restorations. Staining from commonly consumed beverages can impact the appearance of these materials, potentially requiring frequent replacement or repair. Materials and Methods: Three types of ceramic materials—lithium disilicate, zirconia-reinforced lithium silicate, and feldspathic porcelain—were tested. A total of 45 disc-shaped specimens (15 for each material) were fabricated and subjected to staining solutions (coffee, tea, and red wine) for 14 days at 37°C. Color measurements were performed before and after staining using a spectrophotometer, and color differences (ΔE) were calculated based on the CIELAB color system. Statistical analysis was performed using analysis of variance and Tukey’s post-hoc test to compare the groups (P < 0.05). Results: Lithium disilicate ceramics exhibited the least color change (mean ΔE = 2.1 ± 0.5) across all staining solutions, followed by zirconia-reinforced lithium silicate (mean ΔE = 3.2 ± 0.6). Feldspathic porcelain demonstrated the highest color change (mean ΔE = 4.5 ± 0.8), particularly in red wine (mean ΔE = 5.2 ± 0.7). Statistical analysis confirmed significant differences between the groups (P < 0.05). Conclusion: Lithium disilicate ceramics exhibited superior color stability compared to zirconia-reinforced lithium silicate and feldspathic porcelain. These findings suggest that material selection plays a vital role in minimizing discoloration over time, especially in patients with high consumption of staining beverages.